Bridging Educational Change and Social Justice: A Call to the Field. (January 2023) - Datnow, Amanda; Yoshisato, Mariko; Macdonald, Brandie; Trejos, Jessica; Kennedy, Benjamin C.
The education research community, both within the American Educational Research Association (AERA) and beyond, could and should play a critical role in fundamentally transforming educational institutions and systems. Given its complexity, transformative change in education is best undertaken as a collective endeavor. Yet for researchers to be a valuable resource in educational transformation, we will need to bridge knowledge across subfields that currently have limited interaction. Through two illustrative examples, we demonstrate the need to link knowledge on educational change with knowledge on how to create more equitable, anti-racist, and decolonized spaces for formal and informal learning. While operating in different spaces and initiated at different entry points, the two change efforts exemplify a common set of commitments and actionable pathways for achieving transformational change. This article is a call to action for researchers to join together in supporting educational transformation that fundamentally challenges the inequitable arrangements persisting in educational organizations characterized by systemic racism and colonialism. Bridging knowledge bases and being accountable to serve and support communities and their intersectional identities are essential to making deep, scalable changes in education that promote social justice.